Potential role of cofactor of BRCA1 in hepatocellular carcinoma pathogenesis - Youssef, Aya Atef (AUC Knowledge Fountain, 2015)
Hepatocellular carcinoma (HCC) is a devastating tumor characterized by poor prognosis. In Egypt, HCC is the first most common cancer in men and the second most common cancer in women in the year 2012. Still, the molecular mechanisms underlying HCC pathogenesis are not fully identified. This leads to the lack of reliable prognostic markers for HCC. COBRA1 is the cofactor of BRCA1, it is one of the four subunits of the negative elongation factor (NELF) referred to as, NELF-B. NELF complex inhibits transcription elongation via stalling RNA polymerase II. COBRA1 was studied in some types of cancer; in breast cancer it was proved to have a tumor suppressor activity meanwhile, it has an oncogenic role in upper gastrointestinal carcinoma (UGC). In UGC, COBRA1 controls the tumor suppressor trefoil factor 1 (TFF1) expression through regulating activator protein-1 (AP-1) complex trans-activation. COBRA1 binds to AP-1 complex subunits (c-Fos and c-Jun) leading to attenuated TFF1 expression. The main aim of this study was to investigate the role of COBRA1 in HCC progression and whether COBRA1 acts in the studied cell lines through NELF or AP-1 complexes. Four HCC cell lines were studied (HepG2, SNU-449, SNU-398 and SNU-387) in addition to, the immortalized liver cells (MIHA) as a control. The used HCC cell lines are isolated from patients at different stages of the tumor, ranging from early, intermediate and late stage. The expression of COBRA1, the other NELF subunits, c-Fos, c-Jun and TFF1 were examined in the four mentioned cell lines. The mRNAs of COBRA1, NELF subunits (A, C/D and E) and TFF1 were analyzed by semi-quantitative RT-PCR. While the proteins of COBRA1, c-Fos and c-Jun were tested by Western blotting. Our results show that COBRA1 protein was differentially expressed among the tested cell lines. This suggests a potential role of COBRA1 in HCC pathogenesis and development. The other NELF subunits (A, C/D and E) mRNAs were co-dependently expressed in all the tested cell lines. In the three HCC cell lines (HepG2, SNU-449 and SNU-387), c-Fos was expressed in its active phosphorylated form in contrast to c-Jun which was not detected in its active form. TFF1 was only expressed in HepG2 (of early stage HCC) and MIHA cells. In conclusion, COBRA1 was proposed to play a role in HCC progression and development. TFF1 mRNA expression profile was not correlated to that of AP-1 complex subunits proteins which suggested the involvement of other regulatory pathways in TFF1 expression which need further study.